Pengembangan Sistem Integrasi Sapi Pedaging dan Kelapa Sawit Terhadap Pemberdayaan Sumber Daya Manusia di Desa Hanakau Jaya - Pradana, Devi Kusuma; Citra Nurma Yunita; Reza Fahlevi; Rani Saputri; Dewi Lestari; Anggi Kemala; Reni Dwi Agustin (Universitas Muhammadiyah Kotabumi, 2025)
The integration of beef cattle and oil palm is an agricultural model that combines oil palm cultivation and livestock production in one land area. This research was conducted at Hanakau Jaya, Sungkai Utara District. This study proposed to formulating a development strategy for an integrated system of beef cattle and oil palm to empower people in Hanaka Jaya. Data collection was held from 29 April to 5 May. Data collection using qualitative methods in-depth interviews, focus group discussions and questionnaires. Results showed that first, the IFE matrix shows a score 2,534 and the EFE matrix gets a score of 2,855. Second, Based on the IE matrix development of an integrated system for beef cattle and oil palm is in quadrant V which shows the conditions to be hold and maintain. Third, There are several efforts for the development of a beef cattle and palm oil integration system for human empowerment in Hanakau Jaya Village based on the priority of the SWOT matrix analysis such as: a) Open a competent recruitment in the field of animal husbandry as an effort to develop sustainable integration. b) Develop cooperation with the government as an effort to get ease to get capital, farmer training and market both domestically and internationally. c) Improving the health of cows through vaccination efforts, maintaining nutrition in feed, health monitoring and establishing cooperation with medical experts. d) Optimize risk management through the development of mitigation strategies.